Primary extranodal lymphoma: unusual sites - Sujata Singh,; Leena K,; Soumya Surath Panda,; Sandip Kumar Mohanty, (Asian Journal of Medical Sciences, 2023)
Background: Lymphoma arises in lymph nodes. Infiltration of malignant lymphomatous cells in the organs other than lymph node is termed as extranodal lymphoma (ENL). Almost any organ in the body can get affected. The most frequently involved system is gastrointestinal tract, followed by lung, liver, spleen, bone, and skin. Primary central nervous system (CNS) lymphoma is also well documented. Origin of tumor from non-lymph-nodal tissue is termed as primary ENL, whereas hematogenous spread of disease from lymph nodes to extranodal tissue is secondary ENL. Extranodal involvement is more common in non-Hodgkin’s lymphoma (NHL) than Hodgkin’s disease. Aims and Objectives: The aim of the study was to study the prevalence of primary ENLs at unusual sites. Materials and Methods: A prospective study was conducted for a period of 3 years to study the prevalence of primary ENLs at rare sites. Results: In our study, the participants were having a mean age of 50 years and showed a bimodal distribution. A total 16 cases were male (59%) and rest were female (11 cases, 41%). We found that B-symptoms were present in 19 cases (70%) and absent in the remaining. Most of the cases were of B- cell type (20 cases, 74%) and rest were T-cell type (seven cases, 26%). The most common extranodal site being gastrointestinal tract (10 cases, 37%) followed by CNS (four cases, 15%), spleen (two cases, 7%), tonsil (two cases, 7%), and cutaneous site (two cases, 7%). Other less common sites included breast, paranasal sinuses, mediastinum, floor of mouth, nasopharynx, testis, and thyroid. NHL was the only variant present in all the cases. Diffuse large B-cell lymphoma (DLBCL) was the most common variant present in 11 cases (37%). The DLBCL was found to be aggressive in most of the cases with most of them being activated B-cell type, ABC (70%) and rest being Germinal center B-cell type, GCB (30%). Conclusion: A broad spectrum of extranodal organs is involved in various subtype of lymphoma. This study concluded that ENLs can occur at any location. The fact that a lymphoma is a primary ENL may be a factor in the treatment plan and prognosis. The lymphoma subtype B cell or T cell type, and the primary organ or tissue of origin can all be important prognostic factors.